2003
DOI: 10.1002/ajmg.a.20190
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of normal and expanded CAG repeat sizes influences age at onset of Huntington disease

Abstract: Huntington disease (HD) is a neurodegenerative disorder caused by the abnormal expansion of CAG repeats in the HD gene on chromosome 4p16.3. Past studies have shown that the size of expanded CAG repeat is inversely associated with age at onset (AO) of HD. It is not known whether the normal Huntington allele size influences the relation between the expanded repeat and AO of HD. Data collected from two independent cohorts were used to test the hypothesis that the unexpanded CAG repeat interacts with the expanded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 19 publications
(26 reference statements)
7
120
3
Order By: Relevance
“…We use this probability rather than estimated years to diagnosis because preliminary analyses of relationships with striatal volumes and other clinical variables suggests that more linear and thus more easily modeled relationships are likely using the probability scale (Paulsen et al, under review). The difference from parent onset age was calculated by subtracting the participant's current age from the parent's age at disease onset; this number serves as an indirect control for possible additional environmental or minor genetic influences on the age of HD onset (Djousse et al, 2003;Li et al, 2003). Thus, we include parent onset age as a possible source of variance in HVLT-R performance independent of CAG length.…”
Section: Participant Characterizationmentioning
confidence: 99%
“…We use this probability rather than estimated years to diagnosis because preliminary analyses of relationships with striatal volumes and other clinical variables suggests that more linear and thus more easily modeled relationships are likely using the probability scale (Paulsen et al, under review). The difference from parent onset age was calculated by subtracting the participant's current age from the parent's age at disease onset; this number serves as an indirect control for possible additional environmental or minor genetic influences on the age of HD onset (Djousse et al, 2003;Li et al, 2003). Thus, we include parent onset age as a possible source of variance in HVLT-R performance independent of CAG length.…”
Section: Participant Characterizationmentioning
confidence: 99%
“…One obvious advantage to these models is the expression fidelity that results from the CAG repeats being carried in the context of the mouse Htt gene; the variability in tissue distribution and expression levels observed in microinjection-based HD transgenic models (due to transgene copy number variation and position affects resulting from random transgene integration) is eliminated. Like HD patients, these HD knock-in mice also are heterozygous for one wild-type Htt allele and one CAG-expanded allele, an important consideration since the contributions of the remaining wild-type Htt gene to disease in HD patients remain controversial (Aziz et al, 2009;Cattaneo et al, 2005;Djousse et al, 2003;Farrer et al, 1993;Lee et al, 2012;Wexler et al, 1987). A key differentiation among the HD knock-in mouse models reported to date, however, is whether the expanded CAG tract is inserted into an otherwise unaltered mouse Htt exon 1 or into a humanized exon 1 sequence.…”
Section: I3 Knock-in Modelsmentioning
confidence: 99%
“…the phenotype is not more severe in patients homozygote or double-heterozygote mutations in the huntingtin gene, (Wexler et al, 1987;Myers et al, 1989). However, it has been suggested that the larger repeats within the normal range of repeats may mitigate the expression of the disease in the group of patients with large expansions (Djousse et al, 2003). Of note, affected individuals homozygous for a glutamine expansion lying in the premutation range have not been reported.…”
Section: Discussionmentioning
confidence: 99%